Surgical versus dilational tracheostomy in patients with severe stroke: a SETPOINT2 post hoc analysis - Schneider, Hauke; Meis, Jan; Klose, Christina; Ratzka, Peter; Niesen, Wolf-Dirk; Seder, David; Bösel, Julian (Neurocritical care, 2024)
Tracheostomy in mechanically ventilated patients with severe stroke can be performed surgically or dilationally. Prospective data comparing both methods in patients with stroke are scarce. The randomized Stroke-Related Early Tracheostomy vs Prolonged Orotracheal Intubation in Neurocritical Care Trial2 (SETPOINT2) assigned 382 mechanically ventilated patients with stroke to early tracheostomy versus extubation or standard tracheostomy. Surgical tracheostomy (ST) was performed in 41 of 307 SETPOINT2 patients, and the majority received dilational tracheostomy (DT). We aimed to compare ST and DT in these patients with patients.